STRATEGI PENGEMBANGAN USAHATANI DURIAN (Durio zibethinus Murr) DI KECAMATAN SIRENJA KABUPATEN DONGGALA - Nutfah, Siti (JSTT, 2015)
This study aims to analyze the feasibility of farm income durian and durian farm in the village of the District Lende Sirenja and development strategy durian farm in the village of the District Lende Sirenja. The population is farmers who carry out farming durian numbered 35 families. Sampling was done randomly (simple random sampling), the number of samples used as respondents as many as 35 families. Analysis of the data used is SWOT analysis to determine the durian farming development strategy and analysis QSPM to get the best strategy in the development of durian farming. SWOT analysis results show that the strategy of development of durian farm in the village Lende in the position of the quadrant I SO strategy (Strength-Opportunity) supports an aggressive strategy. Implementation of programs that can be applied include: (1) Optimizing the resource potential of land owned by the support of agro-climate, (2) Utilizing the motivation of farmers is high in order to increase the diversification of products processed durian, (3) Utilizing the flesh color yellow, taste sweet and fragrance to enhance the promotion of local durian in order to compete with local durian other, (4) Utilizing experience in support to farm durian Durian Horticulture Development Policy of the Ministry of Agriculture, QSPM Further analysis showed that the best strategy for the development of durian farm in the village of Lende is one strategy that is "Strategies to optimize the potential of land resources owned by the support of agro-climate" with a total value of attractiveness (TAS) amounted to 6,285